2014
DOI: 10.1038/onc.2014.328
|View full text |Cite
|
Sign up to set email alerts
|

P-REX1 creates a positive feedback loop to activate growth factor receptor, PI3K/AKT and MEK/ERK signaling in breast cancer

Abstract: Phosphatidylinositol 3-kinase (PI3K) promotes cancer cell survival, migration, growth, and proliferation by generating phosphatidylinositol 3,4,5-trisphosphate (PIP3) in the inner leaflet of the plasma membrane. PIP3 recruits pleckstrin homology (PH) domain-containing proteins to the membrane to activate oncogenic signaling cascades. Anti-cancer therapeutics targeting the PI3K/AKT/mTOR pathway are in clinical development. In a mass spectrometric screen to identify PIP3-regulated proteins in breast cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 47 publications
4
89
2
Order By: Relevance
“…This is in line with earlier studies that demonstrated RAC1 can directly bind and activate PI3K. [11][12][13] This mechanism adds another layer of complexity in Rac1-PI3K interaction which is known to involve complex feedback loops including actin cytoskeletal and local phosphorylated lipid changes to sustain activation of the pathway. 14 Next we wondered whether the PI3K/AKT pathway in turn exerts any regulatory effects on PREX2.…”
supporting
confidence: 75%
“…This is in line with earlier studies that demonstrated RAC1 can directly bind and activate PI3K. [11][12][13] This mechanism adds another layer of complexity in Rac1-PI3K interaction which is known to involve complex feedback loops including actin cytoskeletal and local phosphorylated lipid changes to sustain activation of the pathway. 14 Next we wondered whether the PI3K/AKT pathway in turn exerts any regulatory effects on PREX2.…”
supporting
confidence: 75%
“…HRG and other ErbB ligands translocate P-Rex1 to the plasma membrane in a PI3K-dependent manner, leading to its activation. The requirement for P-Rex1 in HRG-induced Rac1 activation, ruffle formation, and motility, as well as its role in mammary tumorigenesis, has been unambiguously established by means of RNA interference (RNAi)-mediated loss of function approaches (36,40,43,44). Consistent with the established requirement for G␤␥ subunits in P-Rex1 activation, the GEF is also an effector of GPCRs (45).…”
mentioning
confidence: 52%
“…As pharmacologic agents can have nonspecific effects, future studies using genetic approaches such as dominant negative Rac1 mutants will be helpful to strengthen our conclusion. This observation expands on the role of Rac1 in activating the PI3K pathway as documented recently (29)(30)(31). Additionally, as a well-known modulator of growth signaling, the increase in IGF2 expression in PREX2 mutants is also expected to contribute to the activation of the PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 80%
“…We hypothesized that the increased GEF activity of PREX2 mutants and resulting activation of Rac1 contributes to this activation of Akt based on several reports that have shown Rac1 can activate PI3K/Akt signaling by directly binding to PI3K (29)(30)(31). To test this hypothesis in our model system, we expressed a constitutively active Rac1 construct, Q61L, in primary melanocytes.…”
Section: Prex2 Mutant Tumors Have Markedly Increased Cell Proliferationmentioning
confidence: 99%